Pengaruh Impor, Utang Luar Negeri, Pajak Impor terhadap Cadangan Devisa Indonesia - Nadya Putri Ariyani; Nurul Hasanah (Account : Jurnal Akuntansi, Keuangan dan Perbankan, 2023)
At the beginning of 2020, almost all countries in the world experienced a pandemic due to the covid-19 virus. This pandemic has caused all community activities to be limited, including international trade. With the limitation of all activities both domestically and abroad, the economy in various countries continues to decline. But not for Indonesia, even during this pandemic, Indonesia managed to increase its foreign exchange reserves. The purpose of this study is to analyze the role of imports, foreign debt, import taxes which are factors that affect Indonesia's foreign exchange reserves either partially or simultaneously in the period April 2018 to February 2022. The results show that imports have a positive and significant effect, foreign debt has a positive and significant effect, and import taxes have no effect on Indonesia's foreign exchange reserves. Simultaneously imports, foreign debt, import taxes have a significant effect on foreign exchange reserves. The government and Bank Indonesia must control and maintain the stability of the Indonesian economy, especially for export and import activities.